The Impact of Economic Crisis on Graduates’ Employment and Work (Estudios sobre Educación, 2018)
This article examines the employment and work status of Catalan graduates from public universities, by establishing a comparison between three cohorts of graduates: 2004 (during an expansion), 2007 (starting point of economic crisis), and 2010 (during the crisis). A first descriptive analysis shows that the rise of unemployment has affected graduates differently according to gender, social origin, field of study and work during higher education. A second typological analysis shows a homogeneous structure of occupations among the cohorts. However, starting with the 2010 cohort, the most exposed to the crisis, the absolute number of graduates with the better occupational conditions has declined, whereas the number of graduates in less protected has increased.